2022
DOI: 10.3389/fbioe.2022.856753
|View full text |Cite
|
Sign up to set email alerts
|

One Novel Phantom-Less Quantitative Computed Tomography System for Auto-Diagnosis of Osteoporosis Utilizes Low-Dose Chest Computed Tomography Obtained for COVID-19 Screening

Abstract: Background: The diagnosis of osteoporosis is still one of the most critical topics for orthopedic surgeons worldwide. One research direction is to use existing clinical imaging data for accurate measurements of bone mineral density (BMD) without additional radiation.Methods: A novel phantom-less quantitative computed tomography (PL-QCT) system was developed to measure BMD and diagnose osteoporosis, as our previous study reported. Compared with traditional phantom-less QCT, this tool can conduct an automatic se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Similar PL-QCT was used by Xiongfeng et al [25], with the automatic function of selecting vertebrae, hip, fat, and muscle ROIs and using fat and muscle ROI CT values to calibrate BMD results with high precision.…”
Section: Single-energy Ctmentioning
confidence: 99%
“…Similar PL-QCT was used by Xiongfeng et al [25], with the automatic function of selecting vertebrae, hip, fat, and muscle ROIs and using fat and muscle ROI CT values to calibrate BMD results with high precision.…”
Section: Single-energy Ctmentioning
confidence: 99%
“…Many studies have shown that the Hounsfield unit (HU) values of the bone trabecula obtained by a routine CT can be used to assess osteoporosis [5], such as in the lumbar spine [6][7][8], cervical spine [9,10], thoracic spine [11], femur [12], pelvis [13], and ulna [14]. In clinical practice, chest CT [15], a widely used and highly accessible test, can be used for lung cancer screening and chronic obstructive pulmonary disease detection. Osteoporosis can be predicted using the HU value of the spine measured by chest CT without additional cost and radiation exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Dual-energy x-ray absorptiometry (DXA) and quantitative computed tomography (QCT) have been applied to identify osteoporosis as the gold standard (8). BMD assessed in exact areas of the hip or lumbar spine was commonly utilized to evaluate bone health and fracture risk (9).…”
Section: Introductionmentioning
confidence: 99%